Prosthetic Rehabilitation of Severe Hypodontia: A Clinical Report - Lana A. Shinawi (Journal of King Abdulaziz University: Medical Sciences, 2023)
This case report is a five year recollection outlining the treatment of a 14 year old boy with severe hypodontia presented at the specialist and consultant clinics at the Faculty of Dentistry, King Abdulaziz University. The treatment integrated restorative reconstruction of anterior and posterior teeth with prosthetic removable partial dentures to re-establish the vertical dimension of occlusion. This process resulted in an improvement to patients appearance, esthetics and function as well as a positive impact on the patient’s confidence and self image.